Chemo-protective effect of aqueous extract of the resurrection plant Selaginella involvens (Sw.) Spring on UV-tolerance during spore germination of Pteris argyraea T. Moore - Sathiyakumar C.; Irudayaraj V.; Johnson M. (Journal of Stress Physiology & Biochemistry, 2011)
The present study was aimed to know the effect of aqueous extracts of the resurrection plant, Selaginella involvens (Sw.) Spring on spore germination in Pteris argyraea T. Moore and also to know the ameliorating effect of the extracts on UV-Stress during spore germination of Pteris argyraea T. Moore. Based on the present study it is concluded that the extract of Selaginella involvens, shows growth promoting effect by enhancing the spore germination in Pteris argyraea. Both UV and aqueous extracts of Selaginella involvens enhances germination, but the UV stress results in both physical and morphogenetic abnormalities. It is to be noted that in the extract treated spores, the physical abnormalities are in less frequency when compared to the extract- untreated spores.